2004
DOI: 10.1086/423381
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Caspofungin for Treatment of Invasive Aspergillosis in Patients Refractory to or Intolerant of Conventional Antifungal Therapy

Abstract: Caspofungin demonstrated usefulness in the salvage treatment of IA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
386
1
18

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(422 citation statements)
references
References 39 publications
17
386
1
18
Order By: Relevance
“…The response rate to standard-or high-dose L-AmB, haematologica | 2010; 95(4) © F e r r a t a S t o r t i F o u n d a t i o n caspofungin or voriconazole was already reported to range from 32% to 53%. [24][25][26][27][28][29][30] The percentage of success reported in those studies is lower than that observed in our registry, which ranged from 64% to 82%. This could be explained by the very restrictive criteria for response evaluation in pivotal trials.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 61%
“…The response rate to standard-or high-dose L-AmB, haematologica | 2010; 95(4) © F e r r a t a S t o r t i F o u n d a t i o n caspofungin or voriconazole was already reported to range from 32% to 53%. [24][25][26][27][28][29][30] The percentage of success reported in those studies is lower than that observed in our registry, which ranged from 64% to 82%. This could be explained by the very restrictive criteria for response evaluation in pivotal trials.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 61%
“…Finalmente, respecto a los hongos fi lamentosos, específi camente en el caso de Aspergillus, micafungina y caspofungina sólo tienen estudios en escenarios de rescate (falla de un antimicótico previo) [40][41][42] o en intolerancia 43 .…”
Section: Ensayos Clínicos De Efectividadunclassified
“…De las reacciones medicamentosas observadas en pacientes con caspofungina, así como para las otras equinocandinas, se encuentra descrito usualmente fi ebre (7-17%), exantema (13,8%), escalofríos (5,3%), fl ebitis (3,5%), náuseas (1,8%), y otras anormalidades de laboratorio 27,33 . Para caspofungina se han descrito dos eventos adversos serios como anafi laxia 44 e infi ltrados pulmonares (40), los que se observaron en 11 de 979 pacientes (1,1%).…”
Section: Efectos Adversosunclassified
“…Responses in published reports are of the order of 45% (95% CI 40.2% to 50.3%) (Figure 3). [45][46][47][48] Combination therapy Poor response rates for primary and salvage monotherapy therapy for IFI and the availability of agents with differing mechanisms of action have fueled recent reviews. [49][50][51][52] Arguments for considering combination therapy include enhanced fungal killing (synergy), an enhanced spectrum of activity, prevention of development of resistance, and reduction of drug-related toxicities.…”
Section: Salvage Monotherapymentioning
confidence: 99%